Child maltreatment risk as a function of poverty and race/ethnicity in the USA. (29th January 2018) - Kim, Hyunil; Drake, Brett
Abstract: Background: Child maltreatment is a pressing social problem in the USA and internationally. There are increasing calls for the use of a public health approach to child maltreatment, but the effective adoption of such an approach requires a sound foundation of epidemiological data. This study estimates for the first time, using national data, total and type-specific official maltreatment risks while simultaneously considering environmental poverty and race/ethnicity. Methods: National official maltreatment data (2009–13) were linked to census data. We used additive mixed models to estimate race/ethnicity-specific rates of official maltreatment (total and subtypes) as a function of county-level child poverty rates. The additive model coupled with the multilevel design provided empirically sound estimates while handling both curvilinearity and the nested data structure. Results: With increasing county child poverty rates, total and type-specific official maltreatment rates increased in all race/ethnicity groups. At similar poverty levels, White maltreatment rates trended higher than Blacks and Hispanics showed lower rates, especially where the data were most sufficient. For example, at the 25% poverty level, total maltreatment report rates were 6.91% [95% confidence interval (CI): 6.43%–7.40%] for Whites, 6.30% (5.50%–7.11%) for Blacks and 3.32% (2.88%–3.76%) for Hispanics. Conclusions: We find strong positive associations between official child maltreatment and environmental poverty in all race/ethnicity groups. Our data suggest that Black/White disproportionality in official maltreatment is largely driven by Black/White differences in poverty. Our findings also support the presence of a 'Hispanic paradox' in official maltreatment, where Hispanics have lower risks compared with similarly economically situated Whites and Blacks.